Understanding Implementation Financial Report, Income, Operational Costs And Productivity The Welfare Fishermen - Tantri, Leana; Alansori, Apip (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study aims to analyze the influence of understanding financial statements, income, operational costs, and productivity on the welfare of fishermen in Sungai Sidang Village, Rawajitu Utara District, Mesuji Regency. The background of this study is based on the fact that fishermen in the area still face challenges in terms of economic stability, limited financial knowledge, and low productivity of fisheries businesses. This study uses a quantitative method with data collection through distributing questionnaires to 40 fishermen who were respondents, and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique with the help of SmartPLS software version 4.0 . The results of the analysis show that operational costs and productivity variables have a significant effect on fishermen's welfare, while understanding financial statements and income have no significant effect. The R-square value of 0.787 illustrates that the four independent variables together are able to explain 76.3% of the variation in fishermen's welfare. This finding underscores the importance of cost efficiency and increased productivity as the main strategy in improving the standard of living of fishermen. This study has implications for the formulation of policies and programs for empowering coastal communities that are more targeted.